Global research trends and hotspots on human intestinal fungi and health: a bibliometric visualization study - Gong, Ming; Yu, Huiying; Qu, Hong; Li, Zhexian; Liu, Di (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThis article employs bibliometric methods and visual maps to delineate the research background, collaborative relationships, hotspots, and trends in the study of gut fungi in human diseases and health.MethodsPublications related to human gut fungi were retrieved from the Web of Science Core Collection. VOSviewer, CiteSpace, R software and Microsoft Excel were employed to generate visual representations illustrating the contributions made by countries/regions, authors, organizations, and journals. Employing VOSviewer and CiteSpace, we conducted a comprehensive analysis of the retrieved publications, revealing underlying tendencies, research hotspots, and intricate knowledge networks.ResultsThis study analyzed a total of 3,954 publications. The United States ranks first in the number of published papers and has the highest number of citations and h-index. Mostafa S Elshahed is the most prolific author. The University of California System is the institution that published the most papers. Frontiers In Microbiology is the journal with the largest number of publications. Three frequently co-cited references have experienced a citation burst lasting until 2024.ConclusionAdvancements in sequencing technologies have intensified research into human gut fungi and their health implications, shifting the research focus from gut fungal infections towards microbiome science. Inflammatory bowel diseases and Candida albicans have emerged as pivotal areas of interest in this endeavor. Through this study, we have gained a deeper insight into global trends and frontier hotspots within this field, thereby enhancing our understanding of the intricate relationship between gut fungi and human health.